First Case Report of an Unusual Fungus ( Associated with a Pulmonary Infection in a Drug Injection User - Hiba A Al Dallal; Siddharth Narayanan; Christopher M Jones; Shawn R Lockhart; James W Snyder (SAGE Publishing, 2021)
In contrast to a robust literature on known pathogenic fungi such as Cryptococcus and Aspergillus species that cause pulmonary infections, reports of the uncommon genus Sporopachydermia causing infections are very limited. We present the first case report describing the fungus, Sporopachydermia lactativora as a likely cause of pneumonia in a patient with a history of polysubstance abuse and injection drug use (IDU). The patient recovered following antifungal treatment. The organism was recovered from a blood culture, 3 days post collection. Although CHROMagar was of little value, only yeast-like organisms were observed on cornmeal agar. The organism was not in the matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry database. Definitive identification was achieved using the ribosomal DNA (rDNA) sequence analysis by targeting the ITS1 (internal transcribed spacer 1) region. This case report is intended to promote awareness of this fungus as a potential pathogen, by providing new information that has not yet been reported in the literature, and prompts physician awareness to suspect a fungal infection when managing patients with a history of IDU as a potential source of unique environmental organisms not previously encountered, warranting more comprehensive diagnosis and treatment options.